Preparation of Aun quantum clusters with catalytic activity in β-cyclodextrin polyurethane nanosponges. (20th January 2016) - Vasconcelos, Diego Andrade; Kubota, Tatiana; Santos, Douglas C.; Araujo, Marcia V.G.; Teixeira, Zaine; Gimenez, Iara F.
Highlights: β-CD nanosponges were used as a template for the Au n clusters preparation. PL spectra strongly evidenced n  = 11–15 with a higher amount of the smaller ones. This novel material was applied efficiently as a catalyst in a model reaction. Abstract: Here we report the use of β-cyclodextrin polyurethane nanosponges cross-linked with 1, 6-hexamethylene diisocyanate as a template for the preparation of Au n quantum clusters, by the core-etching of glutathione-capped Au nanoparticles. The study of temporal evolution of the core-etching process using different Au concentrations indicated that formation of Au n clusters embedded in the nanosponge is favored by the use of lower Au concentrations, since it began at shorter times and lead to higher cluster loading. An estimation of the number of Au atoms based on the maximum photoluminescence wavelength suggested that, depending on the Au concentration and the core etching time, clusters with 11–15 atoms were formed. After excluding the possibility of an inclusion complex formation, evaluation of the catalytic activity of nanosponge-loaded Au n clusters toward the reduction of 4-nitrophenol has shown that the reaction is catalyzed by the Au n clusters with no induction time, following the Langmuir–Hinshelwood kinetic model.